Turtles from the Mata Amarilla Formation (Cenomanian), Santa Cruz, Argentina: the southernmost record of Prochelidella - Sterli, Juliana (2021)
The fossil record of Cretaceous turtles in Santa Cruz Province is scarce. Turtles have been reported from the Mata Amarilla Formation (Cenomanian), the Chorrillo Formation (Campanian–Maastrichtian), and the Cerro Fortaleza Formation (early Maastrichtian). In this contribution, we examine all the turtle remains recovered from six localities in the Mata Amarilla Formation, nearby Mata Amarilla Farm (Santa Cruz Province, Argentina). These fossils are housed at the “Padre Molina” Museum in Río Gallegos, Santa Cruz. Most of the smaller carapace and plastral remains are conferred to an indeterminate species, cf. Prochelidella sp., based on the small size, the smooth surface of the plates, the wider than long nuchal plate, the presence of a trapezoidal, longer than wide cervical scute, and the presence of a tear-drop entoplastron. The remaining fragments are attributed to a mid-sized species of an indeterminate Chelidae with no ornamentation and rhomboidal entoplastron (longer than wide). Prochelidella spp. is a group of turtles distributed in Chubut, Río Negro, Neuquén, and Mendoza provinces, ranging from the Aptian to the Maastrichtian. The fossil record of Prochelidella spp. shows two main gaps: 1) late Albian gap; and 2) late Coniacian–Santonian gap. The recognition of cf. Prochelidella sp. in the Austral-Magallanes Basin extends the geographic range of this genus more than 500 km south to the previously known southern-most record of Prochelidella (P. argentinae from the Golfo San Jorge Basin, Chubut).